Effect of Giving Plantains and Ambon Bananas on Muscle Endurance in SSB ESGE Tuban Adolescent Athletes - Sari, Lia Novita; Munir, Miftahul (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2024)
Physical fitness is the body's ability to adjust to physical loads so that it can avoid excessive fatigue. Higher physical fitness can reduce the possibility of muscle fatigue. This study aims to determine the endurance of athletes. The type of research is "Quantitative" with a True experimental design, Two Group Pre-test and Post-test Design. Independent variables are bananas and Ambon bananas, dependent variables are Endurance. Statistical results with the Independent T-Test to test the difference in increasing VO2Max in groups treated with bananas and Ambon bananas in athletes obtained a p value = 0.029 because the p value <0.05 then H1 is accepted. The conclusion is that there is a significant difference between giving bananas and Ambon bananas to increase muscle endurance in athletes seen from the highest average value being bananas.